Effects of delivery risk on futures markets : theory and empirical evidence - Charnwut, Roongsangmanoon (2008)
This dissertation consists of four essays on the effects of delivery risk in futures markets. In this dissertation, the delivery risk is defined as the uncertainty arising from the multiple delivery specifications that causes futures price to diverge from the spot price of the par-delivery asset underlying the futures contract.